Managing natural resources for sustainable livelihoods: uniting science and participation - Pound, B.; Snapp, Sieglinde S.; McDougall, C.; Braun, Ann R. (Routledge, 2003)
Drawing on extensive and varied case studies, this book presents innovative approaches for establishing and sustaining participation and collective decision-making in natural resource management research. It covers a wide range of natural resources – including forests and soils, water and management units such as watersheds and common property areas – and provides practical lessons from analysis and meta-analysis of cases from Asia, Africa and Latin America. It offers insights on how to make research participatory while maintaining rigour and high-quality science at various scales.